Production asymmetry of ντ neutrinos and ν ¯ τ $$ {\overline{ν}}_{τ } $$ antineutrinos from a fixed target experiment SHiP - Rafał Maciuła; Antoni Szczurek; Jakub Zaremba; Izabela Babiarz (Journal of High Energy Physics, 2020)
Abstract We discuss how to calculate cross sections as well as rapidity, transverse momentum and energy distributions of ντ and ν ¯ τ $$ {\overline{ν}}_{τ } $$ produced from the direct D s ± → ν τ / ν ¯ τ $$ D_s^{±}→ ν_{τ }/{\overline{ν}}_{τ } $$ and chain D s ± → τ + / τ − → ν τ / ν ¯ τ $$ D_s^{±}→ τ^{+}/τ^{-}→ ν_{τ }/{\overline{ν}}_{τ } $$ decays in p+96 Mo scattering with proton beam Elab = 400 GeV i.e. at s NN $$ {\sqrt{s}}_{NN} $$ = 27.4 GeV. The τ decays are simulated with the help of the Tauola code and include multiple decay channels of τ in amounts proportional to their branching ratios. In our calculations we include D s ± $$ D_s^{± } $$ from charm fragmentation c → D s + $$ D_s^{+} $$ and c ¯ → D s − $$ \overline{c}→ D_s^{-} $$ as well as those from subleading fragmentation of strange quarks/antiquarks s → D s − $$ D_s^{-} $$ and s ¯ → D s + $$ \overline{s}→ D_s^{+} $$ . The s ≠ s ¯ $$ s\ne \overline{s} $$ asymmetry of the strange quark content of proton is included. The different contributions to D s + $$ D_s^{+} $$ and ν τ / ν ¯ τ $$ ν_{τ }/{\overline{ν}}_{τ } $$ are shown explicitly. We discuss and quantify a not discussed so far effect of asymmetries for production of ντ and ν ¯ τ $$ {\overline{ν}}_{τ } $$ caused by subleading fragmentation mechanism and discuss related uncertainties. A potential measurement of the asymmetry is discussed. Estimates of a number of observed ν τ / ν ¯ τ $$ ν_{τ }/{\overline{ν}}_{τ } $$ in the ν τ / ν ¯ τ $$ ν_{τ }/{\overline{ν}}_{τ } $$ +208Pb reaction, with 2m long target are given with the help of the NuWro program. We refer also to the production of the high-energy (anti)neutrinos in the atmosphere.